Reliability of oscillometric central blood pressure and central systolic loading in individuals over 50 years: Effects of posture and fasting. (February 2018) - Mitchelmore, Andrew; Stoner, Lee; Lambrick, Danielle; Jobson, Simon; Faulkner, James
Abstract: Background and aims: The between-day reliability of oscillometric pulse wave analysis has been demonstrated in a young, healthy population but not in an older sample. This study examined the between-day reliability of the SphygmoCor XCEL in individuals over 50 years. As blood pressure is measured in a range of postures and fasting states (supine/seated, fasted/non-fasted), this study also investigated the effect of these variables on central blood pressure and central systolic loading. Methods: Fifty-one adults (m = 21; age 57 ± 6.4 y) were tested on three mornings in supine and seated conditions and in fasted and non-fasted states. Data was analysed as a whole and for normotensive (n = 25) and hypertensive participants (n = 26). Results: SphygmoCor XCEL demonstrated strong reliability in the whole sample for central systolic and diastolic blood pressures, augmentation index (AIx) and AIx75 (ICC = 0.77–0.95). Significant interaction effects were observed in central diastolic blood pressure, central pulse pressure, augmentation index (AIx) and AIx75 ( p < 0.05; η p 2 = 0.10–0.23). Fasting state had a greater influence on central pressures in a seated than supine posture, but a greater effect on central systolic loading measures in a supine posture. Conclusions: The SphygmoCor XCEL is a reliable tool to assess central haemodynamic variables in an older population. It would be pertinent for clinicians and researchers to record central measures in a supine posture to minimise the effects of food consumption. Conversely, the assessment of central systolic loading should occur in a seated condition to minimise the influence of varying fasting states. Highlights: Effect of posture and fasted state on central blood pressure estimation was observed. Interaction effects for posture and fasted state reported for some central measures. Fasting state had a greater influence on central pressures when seated than supine. Oscillometric wave reflection has acceptable between-day reliability in over 50s. SphygmoCor XCEL may be a suitable tool for clinical use in an older population.